Choice of Food: Preventive Measure during Covid-19 Outbreak - Bhatta, Archana (Europasian Journal of Medical Sciences, 2020)
As the COVID-19 pandemic has affected communities around the globe, people are facing the fear of being infected by it. It is believed that coronavirus disease 2019 is directly associated with an individual’s immune response, with no documented research evidence found yet. But, Covid-19 is genetically similar to Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV), therefore the same immune response is expected for COVID-19. It has also been found that individuals having weaker immune functions are more suspected to infect and have a high fatality rate. Preventive measures such as good personal hygiene, wearing the mask, avoiding crowded places and sick individuals, practicing quarantine and proper choice of food can help an individual to be safe from the risk of current COVID-19 infection. Research findings state that nutrition influences immune strength thereby protecting our body from the attack of pathogens. Increasing the intake of a nutritious diet can help to enhance the immune system and makes an individual less susceptible to diseases, which is also considered as a key factor for the prevention of viral infection like COVID-19. Therefore, the incorporation of foods rich in nutrients that boosts our immunity is one of the possible essential preventive measures to fight with this global crisis. DOI: https://doi.org/10.46405/ejms.v2i1.49